Driving school learning (DSL) - Muna Shafawati, Yusoff (2015)
Driving School Learning(DSL) has been developed to help people to easily understand about signboard and also know how to maintain car when learning from this system. At this time, the teaching and learning at driving school still learn by manual process. This system will make user easy to understand. This is developed to help the user memories easily before take a real test. Through the system, user can learn easily understand the module.